Selected Papers from the 15th Estuarine and Coastal Modeling Conference - Signell, Richard (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The 15th Estuarine and Coastal Modeling Conference provides a venue for commercial, academic, and government scientists and engineers from around the world to present and discuss the latest results and techniques in applied estuarine and coastal modeling. Prospective authors are invited to submit papers on a wide range of topic areas, including:• Pollutant Transport and Water Quality Prediction• Coastal Response to Climate Change• Modeling Techniques and Sensitivity Studies• Model Assessment• Modeling Specific Estuarine and Coastal Systems• Visualization and Analysis• Wave and Sediment Transport Modeling• Modeling of Chemicals and Floatables• Oil Spill Transport and Fate Modeling• Inverse Methods• Circulation Modeling• Facility Siting and CSO Studies• Data Assimilation• Nowcast/Forecast Modeling Systems• Modeling Systems with Strong Buoyancy Forcing• Modeling of Coupled Systems• Risk Analysis (Nuclear Reactors, Flood Forecasting)